POPULASI JAMUR MIKORIZA VESIKULAR-ARBUSKULAR PADA LAHAN BEKAS GALIAN EMAS YANG DIREKLAMASI DENGAN LEGUM TUMBUH CEPAT DIKOMBINASIKAN DENGAN PENUTUP TANAH DAN MIKROBA - Suciatmih Suciatmih (JURNAL PENELITIAN BIOLOGI BERKALA PENELITIAN HAYATI, 2006)
A field work has been carried out to study the population of vesicular-arbuscular mycorrhizal (VAM) fungi on degraded gold mining land that was reclamated with fast growing legume (Enterolobium sp. and Acacia mangium) trees in combination with cover crops (Centrosema pubescen dan Flemingia congesta) and microbe (VAM fungi, Rhizobium sp. and mixed Rhizobium sp. and phosphate solubilizing bacteria) inoculation. Reclamation with fast growing legumes in combination with cover crops and microbe inoculation on the degraded land increased the population of VAM fungi. After 1.5 years, the population of the fungi on the reclamated land increased from 3.4 (control) to 6.1–80.5 spore/g soil. The highest spore population resulted by combination between Acacia mangium, C. pubescen, and VAM fungi (V2I1C1) plot followed by combination between Acacia mangium without cover crop, and VAM fungi inoculation (V2I1C0) plot and combination between Enterolobium sp. without cover crop and mixed Rhizobium and phosphate solubilizing bacteria inoculation (V1I3Co) plot were 80.5, 56.0 and 51.8 respectively.